The integrated care pathway for melanoma: the Istituto Dermopatico dell’Immacolata experience in Rome - Francesco Ricci; Alessio Caggiati; Vincenzo Ziparo; Maurizio Elia; Giandomenico Russo; Stefania D'Atri; Cristina Maria Failla; Annarita Panebianco; Giorgio Annessi; Francesca Passarelli; Marie Perez; Tommaso Tartaglione; et al. (AboutOpen, 2019)
Introduction: The Integrated Care Pathway (ICP) represents a multidisciplinary outline of anticipated care, placed in an appropriate timeframe, to support patients with specific conditions or symptoms. The aim of this paper is to define the ICP for patients with melanoma referring to the “Istituto Dermopatico dell’Immacolata-IRCCS di Roma e Villa Paola” (“Center”). Methods and results: A multidisciplinary group (oncologists, dermatologists, surgeons, pathologists etc.) was defined as well as a facilitator to act as a link between all experts. The first step of ICP development was a review of current practice for patients with melanoma referring to the Center. This first step had the scope to define the multidisciplinary process map (a “picture” of the care plan) for patients with melanoma. The process map defined: i) the activities performed during delivery of care to the patients, ii) the responsibilities for these activities and iii) potential problem areas or opportunities for improvements. The process map formed the basis of the final ICP document. Conclusion: The adoption of melanoma ICP will allow the multidisciplinary group to ensure that clinical guidelines and available evidence are incorporated into everyday practice. (Oncology, HTA & Market Access)